ИСПОЛЬЗОВАНИЕ СОВРЕМЕННЫХ ОБРАЗОВАТЕЛЬНЫХ ТЕХНОЛОГИЙ В ПРОЦЕССЕ ИЗУЧЕНИЯ МЕХАНИКИ ЖИДКОСТЕЙ И ГАЗОВ В СРЕДНЕЙ ШКОЛЕ - Ильина, Л.Ф.; Тажибаева, Д.К. (Изд-во КарГУ., 2009)
Мектептегі физика курсында типтік бағдарлама бойынша сұйықтар мен газдардың механи- касы қарастырылмайды. Бұл бөлім авторлық бағдарлама бойынша физика-математикалық сыныптарда ғана оқылады. Тақырып бойынша эксперимент жасау көп қиындықтар келтіре- ді, өйткені мектептерде керек құрал-жабдықтар жоқ. Компьютерлік лабораториялық тре- нажерлер физикалық виртуалды ортаны жасайды, онда оқушылар нақты құралдар қолдан- бай лабораториялық жұмыстар істей алады. The mechanics of liquids and gases in a school course of physics under typical programs is not considered. It is studied in physical and mathematical classes, basically, under author's programs. Section not traditional, difficult enough, therefore its development without application of modern interactive technologies inconveniently. Special problems arise at carrying out of experiments on a theme, as schools are not arranging the corresponding equipment. The laboratory computer training apparatus creating the virtual physical environment in which schoolchildren could to perform laboratory works, without using the real equipment, but, acquiring the same knowledge and skills, allows solve many problems.
Keywords: использование современных образовательных технологий; процесс изучения механики; механики жидкостей; механика газа; средняя школа